Distribution, origins, impact factors and ecological risks of metallic elements in the sediment from Changhua River estuary, Hainan Island, China - Jiyong Ma; You Gou; Zeheng Chen; Kaizhe Fu; Dongming Wu; Dayu Bian; Jianhua Guo; Shiyou Zhang; Zhuang Xing; Dongxu Jiang (Frontiers in Marine Science)
Within the framework of global biogeochemical cycles, estuaries function as a critical interface that connects terrestrial and marine ecosystems. We assessed the heavy metal pollution risk in the Changhua River estuary area. The assessment focused on pollution characteristics, spatial distribution, and ecological risks, while also identifying potential origins of metallic elements through the application of correlation analysis, principal component analysis (PCA), and Positive Matrix Factorization (PMF) models. The results showed that: (1) Sediments were predominantly sandy and weakly alkaline properties, with significant spatial heterogeneity in metallic concentrations. The concentration of metals, compared to their background values (BVs), could be ranked as: Nearshore: Pb > As > Cd > Cu > Zn > Hg > Ni > Cr; Inshore: Cd > Hg > Pb > Zn > Cu > As > Ni > Cr; Estuary: Pb > Cd > Hg > Cu > Zn > Ni > Cr. Particularly, Cd and Hg in inshore sediments registered a mean concentration surpassing their BVs by 417.95% and 187.33%, respectively. (2) The sampling locations presented varying levels of ecological risk. Moderate ecological risk (150 ≤ RI < 300) accounted for 24.14% of the sites, primarily located in inshore and estuarine areas, while extreme ecological risk (300≤RI) was observed in 6.90% of the sites, concentrated within inshore regions. Hg and Cd were identified as the most hazardous metals. (3) Regarding metallic sources, Hg mainly originated from coal burning, while Pb, Zn, and Cd were likely linked to anthropogenic activities associated with port operations. In contrast, Cr, Ni, and Cu were primarily derived from natural and agricultural sources, and As was mainly associated with the residual accumulation of fertilizers and herbicides. Overall, human activities, including agriculture, aquaculture, and port transport, are the primary origins of metallic contamination in the estuarine sediments. Effective management and regular monitoring of port activities are essential for the governance of the estuarine environment. Such practices can yield valuable insights for continuous risk analysis, thereby supporting the ecological health and resilience of these vital environments.